Strategi Adaptasi Masyarakat terhadap Perubahan Sosial - Nur Khofifatuz Zuhriyah; Lilis Sugandha; Wahyu Hadidarma (LPPM Politeknik Pratama, 2024)
Social change is inevitable in people's lives. Social change can occur due to various factors, both internal and external. Society needs to adapt to social changes in order to survive and develop. Society's adaptation strategies to social change can be divided into two categories, namely adaptive strategies and resistance strategies. Adaptive strategies are strategies that aim to adapt to social change, while resistance strategies are strategies that aim to reject or fight social change. There are various kinds of adaptation strategies that can be carried out by society, such as changes in thought patterns and behavior, changes in social structures, and changes in culture. Appropriate adaptation strategies can help communities overcome the negative impacts of social change and take advantage of existing opportunities.